(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2010)
The aim of this paper is to improve thermal performance of a counter flow microchannel heat exchanger (CFMCHE) by using microencapsulated phase change material slurry (MEPCM suspension) as a cooling fluid instead of pure fluid. The MEPCM suspension used in this paper consists of microcapsules constructed from n-octadecane as a phase change material (PCM) and the shell material is Polymethylmethacrylat, these capsules are suspended in water in a concentration of (0 – 20) %. From the results, using of MEPCM suspensions as a cooling fluid leads to modify thermal performance of a CFMCHE by increasing its effectiveness but it also leads to increase the pressure drop. From heat transfer (thermal performance) point of view it is better to use this type of fluid to increase cooling efficiency of a CFMCHE, but due to extra increase in pressure drop it leads to reduce the overall performance compared with pure fluids. Therefore its application depends on the conditions at which this heat exchanger is used.